Unveiling Sufi Legacies in Dhaka of Bangladesh: A Chronological Discourse on Islamic Heritage - Chowdury, Saeyd Rashed Hasan (Universitas Islam Negeri Mataram, 2024)
Dhaka’s landscape is adorned with centuries-old mosques and shrines, a testament to the enduring legacy of Sufi mystics who propagated Islam in the region. Sufis, Islamic mystics, played a pivotal role in establishing Islam in Bengal. This study delves into the arrival, motivations, and practices of these Sufi figures within Dhaka, Bangladesh. By examining biographies and historical records, it explores how Sufis, through their exemplary character, compassionate outreach, and establishment of social institutions like khankahs and dargahs, profoundly influenced the spread of Islam. Even in the face of persecution, the Sufis’ dedication laid the foundation for a new social order, shaping the region’s religious landscape for centuries. Their willingness to engage with Hindu and Buddhist communities on social and spiritual matters fostered a peaceful acceptance of Islam, leading to a significant shift in the region’s religious makeup. By examining Sufi activities, this research sheds light on the historical processes that shaped Dhaka’s religious identity and offer valuable insights for understanding Islamic propagation dynamics.